The Influence of Teachers’ Understanding of the Merdeka Curriculum and Instructional Technology Skills on Its Implementation: The Moderating Role of Differentiated Instruction - Iman Subhi; Noor Hudallah (Universitas Negeri Semarang, 2026)
This study analyzes the effects of teachers’ understanding of the Merdeka Curriculum and their ability to use instructional technology on the implementation of the Merdeka Curriculum, with differentiated instruction conceptualized as a moderating variable. Grounded in curriculum implementation theory, pedagogical content knowledge, technological pedagogical content knowledge, and differentiated instruction theory, this study addresses a research gap that has traditionally treated curriculum understanding, technology, and pedagogical practice as separate domains. This quantitative study involved 207 elementary school teachers in Sirampog District, Brebes Regency, as the research sample. Data were collected using Likert-scale questionnaires and analyzed using Partial Least Squares–Based Structural Equation Modeling (PLS-SEM). The results indicate that teachers’ understanding of the Merdeka Curriculum does not have a direct effect on curriculum implementation but exerts a significant indirect effect through differentiated instruction. Teachers’ ability to use instructional technology has a direct and significant effect on both curriculum implementation and differentiated instruction. Differentiated instruction demonstrates the strongest influence and functions as a mediating rather than a moderating variable, bridging the effects of curriculum understanding and technological competence on Merdeka Curriculum implementation. This study advances the Synergistic Curriculum Implementation Model (SCIM), which suggests that the success of the Merdeka Curriculum is determined by the synergy among curriculum understanding, mastery of instructional technology, and differentiated instructional practices. These findings offer important theoretical and practical implications for policy development and the strengthening of teacher capacity in implementing the Merdeka Curriculum.